Tungsten heavy alloy: an alternative plasma-facing material in terms of hydrogen isotope retention. (29th October 2020) - Maier, H.; Neu, R.; Schwarz-Selinger, T.; von Toussaint, U.; Manhard, A.; Dürbeck, T.; Hunger, K.
Abstract: We performed a systematic study of the deuterium retention in the tungsten heavy alloy W-2Ni-1Fe (HPM 1850 from HC Starck, Germany). Consisting of two different phases with generally two distinctly different heats of solution, such alloys represent a special class of materials with respect to hydrogen isotope transport and retention. Deuterium was implanted from a plasma with an energy of 38 eV D −1 at sample temperatures of 100 °C, 175 °C, and 250 °C in the fluence range 10 23 D m −2 to 4 × 10 25 D m −2 . For each combination of implantation temperature and fluence, two alloy samples were exposed together with one sample of bulk hot-rolled tungsten (from Plansee SE). The amount of retained deuterium was determined by thermal desorption with heating up to 850 °C for the alloy and 1050 °C for the bulk tungsten. The outgassed deuterium was detected by mass spectroscopy at the mass channels 3, 4, 19, and 20 corresponding to HD, D2, HDO, and D2 O, respectively. The near-surface deuterium concentration was determined by 3 He nuclear reaction analysis. The retention in the alloy as compared to the bulk tungsten decreases systematically with increasing implantation fluence for each of the investigated implantation temperatures. For the higher fluences the ratio decreases systematically also, as a function of implantation temperature. This means that especially for high implantation fluences and temperatures the alloy HPM 1850 systematically retains less hydrogen isotopes than bulk tungsten. This property represents an important qualification criterion as a plasma-facing material for a future fusion reactor.